HUBUNGAN KOMUNIKASI ORANGTUA DAN REMAJA DENGAN PENGGUNAAN NAPZA DI LEMBAGA PEMASYARAKATAN ANAK PEKANBARU TAHUN 2015 - Rika, Febrianti (Universitasdiwangsa Jambi, 2015)
Teens have a turbulent life, resulting in violation of norms, one violation of norms onadolescents is drug dependence. Abbreviation drug of Narcotic, Psychotropic, and OtherAddictive substances is medicine, material, or substance is not food if going into humanbody can be effect, especially in the brain that can lead to dependency. One of the causesdrug use at adolescent is the lack of good communication from parent and teens.Communication is a process of human interaction with various forms or ways to conveyinformation or for a particular purpose. Purpose of this research is to know is there relationcommunication parent and adolescent with drug use at Prisons Children Pekanbaru 2015.This research method using quantitative research with analytic design and cross sectionalapproach and conducted in Februari – March 2015 in the Prisons Children Pekanbaru.Population in this study were as many as 45 teenagers and sample are taken totalpopulation is 45 teens from primary data (questionnaires). Data analysis is of univariate andbivariate analysis with chi – square test. Of the univariate analysis of 45 adolescents mostlyuse drugs the 26 teenagers (58%). And of 26 adolescents who communication lack good 15teenagers (58%) and a good 11 teenagrs(42%). Obtained from the chi-square test was nosignificant association between communication from parent and adolescent with drug use.Researcher hope that this study can be used as a comparison and baselines to plus orsupplemented in the future with different independent variables and sample more.